Begg class II treatment planning for optimum profile control - Thompson F.G (Sciendo, 1982)
In attempting to obtain the treatment goals of a normal incisor and lip relationship the overall facial appearance may worsen in a number of patients during treatment with the Begg appliance. The three main causes of this deteriorating profile are over-retraction and excessive torquing of upper incisors, retraction of the lower incisors, and the effect of backward rotation of the mandible. A sequence of clinical cases are used to illustrate these adverse effects. Suggested methods are given for limiting the treatment effects of Begg mechanotherapy by selection of appropriate extraction sites and/or by combined use of Begg mechanics with different headgear forces.